A Female Psoriatic Arthritis Patient Involving the TMJ - Giovanni Falisi; Roberto Gatto; Carlo Di Paolo; Alberto De Biase; Carlo Franceschini; Annalisa Monaco; Sofia Rastelli; Gianluca Botticelli (Case Reports in Dentistry)
Psoriatic arthritis (PsA) is an inflammatory chronic arthritis associated with psoriasis. Currently, data about gender differences in clinical manifestation and therapeutic outcomes of PsA are limited. Frequently, women manifest a peripheral disease while men have an axial localization. Moreover, women display higher disease activity and physical activity limitations, if compared to men. Although the involvement of the temporomandibular joint (TMJ) is quite rare, it can seriously impact the quality of life. The morpho-functional peculiarities of TMJ require a multidisciplinary approach to perform a correct diagnosis and a successful treatment. Here, we report a case of a woman affected by PsA involving TMJ treated by combining pharmacological therapy and an occlusal splint. The coordination between different specialties led to a complete remission of clinical symptoms and a regression of lesions.